Investigating the Economic Situation of Iran, Turkey, and the UAE before and after Emergence of Corona Virus Through a Comprehensive Overview of Global Economic Indicators - Safarchi, Saman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The role of health as a determinant component of human capital for well-being and consequently as a key factor of economic growth has been the subject of major research attention (Alsan et al., 2006). In this regard, the need for conducting scientific research to find out how all economic indicators will be impacted by COVID-19 pandemic is undeniable to be as a guideline for the governments for adjusting its policies to alleviate the economics losses of the global pandemic. In order to come up with statistically meaningful findings, E-Views software is used as the program for data analysis. The data is gathered from the World Bank database as well as Trading Economics. Three time series data developed for three separate countries during a time period between 2000 and 2019 which encompasses four indicators. Hence, totally 20 observations were used for each indicator and for every country separately in the analysis. GDP Growth (annual percentage growth rate of GDP at market prices), Inflation Rate (GDP deflator), Unemployment Rate, and Human Development Index (HDI) were our four indicators. GDP Growth was considered as dependent variable and three others are taken as independent or explanatory variables. The assumption is that GDP growth would be influenced by the changes in the independent variables. Then, for choosing country, we decided to select countries on the basis of HDI in a way that each country can be a representative country for low, medium, and high HDI group. Based on the results of the analyses, with respect to the Iran’s outcomes, HDI is the only variable that has significant effect on GDP Growth and this effect is positive as expected. With regard to the Turkey, out of three independent variables, Unemployment Rate and HDI have significant effect on GDP Growth with negative and positive impact accordingly. When it comes to the UAE, it can be seen that all three independent variables have significant effect on GDP Growth. Additionally, the investigation of economic situation of three countries reveals that those countries that have higher Human Development Index (HDI) before COVID-19 pandemic have better statistics after COVID-19 pandemic; specifically, less decrease in GDP Growth, less increase in Unemployment Rate, and less increase in Inflation Rate relative to countries with lower HDI. Thus, as expected, for the time being, UAE has the best situation relative to the other two countries.

ÖZ: Beşeri sermayenin belirleyici bir bileşeni ve devamı büyümenin kilit bir faktör olarak sağlığın rölesi, araştırmanın büyük konusu olmuştur (Alsan ve diğerleri, 2006). Bu bağlamda, tüm ekonomik göstergelerin COVID-19 pandeminden nasıl etkileneceğini bulmak için araştırma yapma ihtiyacını, hükümetler için politikalarını hafifletmek için ayarlamaya yapılacak neleri külbütör içinde bir kılavuz olması yadsınamaz. küresel pandeminin ekonomik kayıpları. İstatistiksel olarak anlamlı bulgular ortaya çıkarmak için veri analizi programı olarak E-Views yazılımı kullanılmaktadır. Veriler, Dünya Bankası veri tabanından ve Ticaret Ekonomisinden toplanır. 2000 ile 2019 arasındaki bir dönemde üç ayrı ülke için geliştirilen ve dört göstergeyi içeren üç zaman serisi verisi. Bu nedenle analizde her gösterge ve her ülke için ayrı ayrı toplam 20 gözlem kullanılmıştır. GSYİH Büyüme (GSYH'nin piyasa fiyatlarına göre yıllık yüzde büyüme oranı), Enflasyon Oranı (GSYİH deflatörü), İşsizlik Oranı ve İnsani Gelişme Endeksi (İGE) dört göstergemizdi. GSYİH Büyümesi bağımlı değişken olarak kabul edildi ve diğer üçü bağımsız veya açıklayıcı değişkenler olarak alındı. Varsayım, GSYİH büyümesinin bağımsız değişkenlerdeki değişikliklerden etkileneceğidir. Daha sonra ülke seçimi için İGE bazında her ülkenin düşük, orta ve yüksek İGE grubu için temsili ülke olabileceği şekilde ülkeleri seçmeye karar verdik. Analiz sonuçlarına göre İran'ın çıktılarına ilişkin olarak İGE, GSYİH Büyümesi üzerinde önemli etkiye sahip tek değişkendir ve bu etki beklendiği gibi olumludur. Türkiye ile ilgili olarak, üç bağımsız değişkenden İşsizlik Oranı ve İGE'nin GSYİH Büyümesine önemli etkisi var ve buna bağlı olarak olumsuz ve olumlu etki yapıyor. BAE'ye gelince, her üç bağımsız değişkenin de GSYİH Büyümesi üzerinde önemli etkiye sahip olduğu görülebilir. Ek olarak, üç ülkenin ekonomik durumunun incelenmesi, COVID-19 pandemisinden önce daha yüksek İnsani Gelişme Endeksi (İGE) olan ülkelerin COVID-19 pandemisinden sonra daha iyi istatistiklere sahip olduğunu ortaya koymaktadır; özellikle, daha düşük İGE'ye sahip ülkelere göre GSYİH Büyümesinde daha az azalma, İşsizlik Oranında daha az artış ve Enflasyon Oranında daha az artış. Dolayısıyla, beklendiği gibi, şimdilik BAE diğer iki ülkeye göre en iyi duruma sahip.
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2020. Supervisor: Prof. Dr. Melek Şule Aker
Keywords: Business Administration Department; Covid 19 Pandemic--Economic Conditions--Iran; Covid 19 Pandemic--Economic Conditions--Turkey; COVID-19 Pandemic, GDP Growth, Unemployment Rate, Inflation Rate, HDI, Iran, Turkey, UAE